The Effect of Financial Literacy, Capital Market Knowledge, and Perceived Risk on Students Investment Interest (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the influence of financial literacy, capital market knowledge, and risk perception on the investment interest of students majoring in Management at the Faculty of Economics, State University of Medan. This study uses a quantitative approach through a survey method involving 67 respondents selected by purposive sampling, namely students from the class of 2022 who have attended the Capital Market School (SPM). The research instrument was declared valid and reliable, while data analysis was performed using multiple linear regression supported by classical assumption tests. The results showed that financial literacy did not have a significant effect on investment interest, capital market knowledge had a positive and significant effect, while risk perception did not have a significant effect. Simultaneously, all three variables had a significant effect on investment interest, with the model explaining 71.5% of the variation in interest. This study is novel in its use of SPM participation criteria in determining the sample and implies the need to strengthen capital market education to increase student investment interest.